2021
DOI: 10.1002/mop.32811
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy improvement for multimetal analysis by laser‐induced breakdown spectroscopy with least squares support vector machine

Abstract: An efficient method has been developed to analyze metal species by using laser‐induced breakdown spectroscopy (LIBS). A least squares support vector machine (LSSVM) was applied to quantitative analysis of multimetal samples with different matrix content, as LSSVM can select the input variables and convert the mapping to the feature space to obtain the linear performance. In this work, three kinds of metal species (alloy steel, ferrochromium alloy, and ferromanganese alloy) were used to construct the LSSVM mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Che et al 15 improve the accuracy of multitetal analysis with LIBS and least squares support vector machines. Dai et al 16 identified aluminum alloy by LIBS combined with machine algorithm. Sirven et al 17 used LIBS combined with neural networks to perform qualitative and quantitative analysis of chromium-contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…Che et al 15 improve the accuracy of multitetal analysis with LIBS and least squares support vector machines. Dai et al 16 identified aluminum alloy by LIBS combined with machine algorithm. Sirven et al 17 used LIBS combined with neural networks to perform qualitative and quantitative analysis of chromium-contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in qualitative elemental analysis. 7,8 However, its reliability is relevant to the laser properties, substrates, and ambient surroundings. 9 Furthermore, it is important to measure accurate temperature for improving the application of LIBS.…”
Section: Introductionmentioning
confidence: 99%
“…where b refers to the regression coefficient, and e refers to the residual matrix of the model. The least squares support vector machine (LS-SVM) 23,24 is a machine learning method developed on the basis of statistical learning theory. The key parameter indexes of LS-SVM are input vectors, kernel function types, and corresponding parameters.…”
Section: Experimental Equipment and Parametersmentioning
confidence: 99%